Rheumatoid arthritis is associated with rs17337023 polymorphism and increased serum level of the EGFR protein - Huang, Chung-Ming; Chen, Hsin-Han; Chen, Da-Chung; Huang, Yu-Chuen; Liu, Shih-Ping; Lin, Ying-Ju; Chang, Yuan-Yen; Lin, Hui-Wen; Chen, Shih-Yin; Tsai, Fuu-Jen (PloS one, 2017)
We have previously described the association of rheumatoid arthritis (RA) prevalence and two epidermal growth factor receptor (EGFR) SNPs (rs17337023 and rs2227983) among the Taiwanese population. This present study aimed to elucidate whether the SNPs can alter the expression of EGFR in the progression of RA. The cohort study included 366 Taiwan's Han Chinese RA patients and 326 age and gender matched healthy controls. Blood samples collected from the participants were analyzed to determine their serum EGFR levels and to identify EGFR SNPs from their genomic DNA. Genotyping for EGFR SNPs was performed by restriction fragment length polymorphism (RFLP) assay. The relationship between EGFR SNP and the clinical manifestations of RA was evaluated. Our results showed that a statistically significant difference in genotype frequency distributions at rs17337023 SNP for RA patients and controls (p ˂ 0.05). In addition, compared with the haplotype frequencies between case and control groups, the RA patient with the GT haplotype appeared to be a significant "protective" haplotype compared with other haplotypes (OR: 0.73, 95% CI: 0.59-0.91; p = 0.005). Furthermore, the increased serum level of EGFR was also observed in RA patients (p ˂ 0.001). Our study showed that RA is associated with rs17337023 SNP in EGFR gene and increased serum level of the EGFR protein. These findings suggest EGFR is worthy of further investigation as a therapeutic target for RA.